The Impact of Surface Roughness on Hydrodynamic Coefficients for a Fixed Vertical Cylinder - Abdul Fattah, Muhamad Zulfadhli (IRC, 2019)
Wave force is a major component of the total force subjected to the structure and an accurate estimation of such loads will indefinitely lead to a more cost-effective design. However, the random nature of ocean waves has made it difficult for designers to include its non-linear properties in calculations. On top of that, natural phenomena such as the accumulation of marine growth may increase hydrodynamic loadings subjected to the structure.